Peningkatan Motivasi Belajar melalui Permainan Kecil dalam Pemanasan pada Pembelajaran PJOK Kelas VI SDN Bawang 1 Kota Kediri: Penelitian - Rahmadani Melia ZalzaBilla; Ardhi Mardiyanto Indra Purnomo; Mohammad Yunan Firmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Students' learning motivation in Physical Education, Sports, and Health (PJOK) often faces obstacles due to monotonous and less varied teaching methods. This study aims to enhance students' learning motivation through the small games approach during the warm-up session before learning activities. The method used is Classroom Action Research (CAR) based on the Kemmis & McTaggart model, involving 27 sixth-grade students from SDN Bawang 1 Kota Kediri. This study was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The results show that the small games approach during warm-ups effectively increases students' motivation. In the first cycle, 48.1% of students strongly agreed with the warm-up game method, and this figure increased to 62.9% in the second cycle. Additionally, the average learning motivation score improved from 2.33 to 2.59. This improvement indicates that using small games enhances student engagement, readiness, and enthusiasm in PJOK learning. Based on these findings, it can be concluded that implementing small games in warm- ups positively impacts students' learning motivation. This method helps create a more enjoyable, interactive, and engaging learning environment, encouraging students to be more active in class. Therefore, this approach is recommended as an innovative teaching strategy for PJOK teachers to improve the effectiveness of learning in elementary schools.